Nanoneuroscience Structural and Functional Roles of the Neuronal Cytoskeleton in Health and Disease - Woolf, Nancy J.; Priel, Avner; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
Nanoneuroscience is the study of computationally relevant biomolecules found inside neurons. Because of recent technological advances at the nanometer scale, scientists have at their disposal increasingly better ways to study the brain and the biophysics of its molecules. This book describes how biomolecules contribute to the operations of synapses and perform other computationally relevant functions inside dendrites. These biomolecular operations considerably expand the brain-computer analogy - endowing each neuron with the processing power of a silicon-based multiprocessor. Amazingly, the brain contains hundreds of billions of neurons.
Introducing Nanoneuroscience as a Distinct Discipline -- Nanoscale Components of Neurons: From Biomolecules to Nanodevices -- The Cytoskeleton as a Nanoscale Information Processor: Electrical Properties and an Actin-Microtubule Network Model -- Nanocarriers and Intracellular Transport: Moving Along the Cytoskeletal Matrix -- Nanotechnology, Nanostructure, and Nervous System Disorders -- Novel Modes of Neural Computation: From Nanowires to Mind.
Keywords: Nanotechnology; Neurobiology; Biophysics; Biological physics; Biomedical engineering; Nanotechnology; Neurobiology; Biological and Medical Physics, Biophysics; Biomedical Engineering and Bioengineering